What is didactics of history (today)? - Zdeněk Beneš (Czech Pedagogical Society, 2011)
The paper focuses on the status of the discipline of didactics of history, ofschool history and in a wider context of field didactics of social sciences and humanities.The difference between a piece of information and fact about history as well as thedifference of between popularising and didactic depicting of social (historical) realityare discussed. From these differences, one of the basic characteristics of these didacticsis induced; an implicit openness to information of the system of their subject matter,which leads to an increase of the importance of interpretation. It is interpretation thatmust be seen as the central point of noetic and educational function of these didacticsand the school subjects that they are connected to.